An evaluation of the teacher appraisal system in current use at Kapiti College : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Educational Administration at Massey University, - Ryan, Peter Martin (Massey University, 2000)
Kapiti College changed its teacher appraisal system over the last two years from a peer appraisal model to a hierarchical model. This research examines the reasons for the introduction and refinement of teacher appraisal in education sectors, predominantly in New Zealand secondary schools, but within the context of other English-speaking nations. A review of the literature on the topic indicates that there is a great deal of disagreement about the value of teacher appraisal, depending on the way in which teaching itself is regarded. Even for those who do recommend the use of teacher appraisal, there remains the issue of ascertaining the purposes of this appraisal. Is it possible, for example, to combine appraisal for professional development with appraisal for accountability? This literature review generated twelve research questions. A survey of the teachers employed at Kapiti College, an analysis of school documents and an interview with the principal provided the following information based on these twelve questions. Professional development was under-emphasised because of external time-constraints, due to the emphasis on remuneration. It would be relatively simple to strengthen the links between the appraisal system and professional development for individual teachers. Focus on teacher competence was generally seen as the least important aspect of the new process. However, there were some findings that indicated that teachers believed that the division between competence procedures and appraisal was not well-defined. Most teachers considered their own appraisal process to have been done fairly. Most also had reservations about how fair it would be for others. The principal and staff were all well aware of the impact of the new system on the culture of the college. Not all appraisers felt confident or well-prepared in their role of appraising others, and so there was some damage done to professional relationships. Nevertheless, there was also considerable growth for many people, with positive and focused professional discussion on matters of importance to the appraisee. It is difficult to see how an improvement in student learning could be directly ascribed to a change in teacher appraisal, because educational changes do not happen in an isolated fashion. The new principal had already begun the change process towards a hierarchical system when this change was imposed externally and accelerated. The principal regarded the change as very important. In general, the staff did not regard it as very important. Because the pace of change was accelerated on account of external requirements, the change was not managed as well as it could have been. There was a distinct difference in the knowledge of the change process between those who were appraisees only and those who were both appraisers and appraisees. A number of appraisers gained new information but most appraisees did not consider that they had learnt anything new about their teaching. A small majority of teachers considered that the time spent on appraisal was worthwhile. Summative comment. New Zealand law now requires a teacher appraisal system. There were many strengths to the system implemented at Kapiti College in 2000. Some refinements could now be made to strengthen the professional aspect of appraisal. These could include: • Discussion by all staff of the nature of teaching and, consequently, of key factors in a teacher appraisal system. • Training of appraisers in dealing with the "hard issues". • The development of stronger systems for professional supervision of teachers. These systems should be quite distinct from teacher appraisal. • Development of stronger links between teacher appraisal and individual professional development. • A change of frequency for teacher appraisal to once every two years.
Keywords: Teacher appraisal; Kapiti College; Secondary schools, New Zealand; Secondary school teachers